An Overview on Current Researches on Underwater Sensor Networks: Applications, Challenges and Future Trends - Pedram Vahdani Amoli (Institute of Advanced Engineering and Science, 2016)
Nowadays, Underwater Sensor Networks (UWSN), in which data is collected through underwater sensors, have drawn lots of concern. Generally, wireless sensor network (WSNs) have important applications such as remote environmental monitoring and target tracking. This possibility is enabled by the available smaller and cheaper sensors. These sensors are equipped with wireless interfaces which they form a network. However, there are various problems specified to underwater environments, including the communication medium. Designs of these types of networks significantly depend on their application, and factors such as environment, design objectives of the application, cost, hardware and system constraints. The goal of this work is to review the literature on various aspects of UWSNs, and present an overview of several new applications and their challenges on UWSN. Publications are reviewed to show the statistics of published works in several aspects.